2011
DOI: 10.1371/journal.pone.0023864
|View full text |Cite
|
Sign up to set email alerts
|

Asthmatics Exhibit Altered Oxylipin Profiles Compared to Healthy Individuals after Subway Air Exposure

Abstract: BackgroundAsthma is a chronic inflammatory lung disease that causes significant morbidity and mortality worldwide. Air pollutants such as particulate matter (PM) and oxidants are important factors in causing exacerbations in asthmatics, and the source and composition of pollutants greatly affects pathological implications.ObjectivesThis randomized crossover study investigated responses of the respiratory system to Stockholm subway air in asthmatics and healthy individuals. Eicosanoids and other oxylipins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 57 publications
3
52
0
Order By: Relevance
“…In particular, the 12/15-LOX derived 9-and 13-hydroxyoctadecatrienoic acid (HOTE) and their corresponding keto-trienes, oxooctadecatrienoic acids (KOTEs) could be of interest. We observed that the levels of 9-and 13-HOTE in BAL-fluid were significantly increased in healthy individuals compared to mild asthmatics following exposure to subway air, suggesting that these compounds may potentially play a role in the inflammatory response and/or subsequent resolution, and that this response is distinct in healthy individuals versus asthmatics (unpublished data [251]). …”
Section: -3 Fatty Acid-derived Oxylipinsmentioning
confidence: 72%
See 1 more Smart Citation
“…In particular, the 12/15-LOX derived 9-and 13-hydroxyoctadecatrienoic acid (HOTE) and their corresponding keto-trienes, oxooctadecatrienoic acids (KOTEs) could be of interest. We observed that the levels of 9-and 13-HOTE in BAL-fluid were significantly increased in healthy individuals compared to mild asthmatics following exposure to subway air, suggesting that these compounds may potentially play a role in the inflammatory response and/or subsequent resolution, and that this response is distinct in healthy individuals versus asthmatics (unpublished data [251]). …”
Section: -3 Fatty Acid-derived Oxylipinsmentioning
confidence: 72%
“…However, these compounds warrant analysis because alterations may occur that are due to active biological functions or effects caused by alterations in the 13-and/or 9-HODE precursors. We have for instance observed elevated levels of these compounds in BAL-fluid from healthy individuals following subway air exposure that correlate with shifts in HODE and KODE levels (unpublished data [251]). …”
Section: Hydroxyoctadecadienoic Acids (Hodes) Oxooctadecadienoic Acimentioning
confidence: 83%
“…The role of lipid mediators in the pathogenesis of asthma has been extensively studied [4][5][6][7][8][9][10]. Lipid mediators are included in a group of compounds broadly called oxylipins, a term that includes eicosanoids derived from arachidonic acid as well as compounds derived from other related v-3 and v-6 fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Oxylipin profiles have previously been investigated in large-volume bronchoalveolar lavage fluid (BALF), mainly reflecting profiles in the peripheral lung [7,8], but not in small-volume bronchial wash samples, which better reflect the proximal airways. To test the hypothesis that asthmatics, due to their underlying asthmatic inflammation, have altered oxylipin profiles in both distal (BALF) and proximal (bronchial wash) regions of the lung compared with healthy individuals, bronchoscopies were performed.…”
Section: Introductionmentioning
confidence: 99%
“…DHA and EPA), most of which have as of yet undetermined biological roles. The use of LC with low particle size and MRM mass spectrometry has recently made it possible to quantify hundreds of these molecules simultaneously [98,99], providing new insights into their role in respiratory disease [80]. A particular advantage of analysing eicosanoids is that measurement of indicative urinary metabolites is usually a sensitive approach to monitoring pulmonary biosynthesis.…”
Section: Eicosanoidsmentioning
confidence: 99%